Restoration of Good Name (Rehabilitation) of Perpetrators of Environmental Crimes Within the Scope of The Corporation After the Free Verdict (VRIJSPRAAK) - Imam Mukhlish Ash Shiddiq (Jurnal Impresi Indonesia, 2025)
The restoration of reputation for environmental crime perpetrators after a not guilty verdict (vrijspraak) is a crucial issue in corporate law in Indonesia. Although companies are declared innocent, negative stigma and reputational damage persist, affecting consumer and investor trust. This study examines the rehabilitation mechanisms available for corporations post-verdict, as well as the challenges faced in restoring their reputation. The research employs a literature study using a normative legal approach, analyzing relevant regulations and legal cases. The findings indicate that despite existing regulations supporting rehabilitation, their implementation is often inconsistent, especially for corporations. Reputation recovery can be pursued through Corporate Social Responsibility (CSR) programs and environmental certifications. This study recommends strengthening rehabilitation regulations for more effective outcomes, ensuring justice and legal certainty.